Effects of RMP-induced changes of radial electric fields on microturbulence in DIII-D pedestal top. (5th February 2019) - Taimourzadeh, S.; Shi, L.; Lin, Z.; Nazikian, R.; Holod, I.; Spong, D.
Abstract: Gyrokinetic simulations of DIII-D tokamak with axisymmetric equilibrium show that the reduction in the radial electric field shear at the top of the pedestal during edge localized mode (ELM) suppression with the n   =  2 resonant magnetic perturbations (RMPs) leads to enhanced drift-wave turbulence and extended turbulence spreading to the top of the pedestal relative to ELMing plasmas with similar RMP and pedestal parameters. The simulated turbulent transport at the top of the pedestal in ELM suppressed conditions is consistent with experimental observations of enhanced turbulence at the top of the pedestal during ELM suppression by the RMPs. These results imply that enhanced drift-wave turbulence due to reduced shear at the pedestal top can contribute to the additional transport required to prevent the pedestal growing to a width that is unstable to ELMs.